Perlindungan Hukum Terhadap Pekerja Akibat Tidak Dibayarkannya Iuran BPJS Ketenagakerjaan Oleh Perusahaan : Studi Kasus Putusan Nomor 40/Pdt.G.S/2023/PN Pbr - Satria Yuritama; Nurhayani Nurhayani (Pusat Riset dan Inovasi Nasional, 2026)
BPJS Ketenagakerjaan aims to protect workers and ensure their welfare. However, in reality, many companies do not register some or all of their workers, which affects the welfare of workers and has the potential to impact the social security system as a whole. The research questions are: How does the non-payment of BPJS Ketenagakerjaan contributions affect workers' rights in relation to the theory of legal protection in Decision Number 40/Pdt.G.S/2023/PN Pbr and How the mechanism for fulfilling workers' rights when a company that has previously defaulted on its contributions has paid off its obligations. This research is normative-empirical, using three approaches, namely legislation, case studies, and legal sociology. The results show that the arrears in this case not only caused workers to lose access to JKK, JKM, JHT, and JP program benefits, but also placed them in economic and social vulnerability because they did not receive compensation when employment risks occurred. After the company has fulfilled its obligations, the membership and service team will verify the payment and reactivate the participant's status so that workers can reapply for claims, thereby ensuring that workers' rights are promptly fulfilled both administratively and substantively.